Seizure Susceptibility Corrupts Inferior Colliculus Acoustic Integration - Pinto, Hyorrana Priscila Pereira; de Oliveira Lucas, Eric Levi; Carvalho, Vinícius Rezende; Mourão, Flávio Afonso Gonçalves; de Oliveira Guarnieri, Leonardo; Mendes, Eduardo Mazoni Andrade Marçal; de Castro Medeiros, Daniel; Moraes, Márcio Flávio Dutra (Frontiers in Systems Neuroscience, 2019)
Evidence suggests that the pathophysiology associated with epileptic susceptibility may disturb the functional connectivity of neural circuits and compromise the brain functions, even when seizures are absent. Although memory impairment is common comorbidity found in patients with epilepsy, it is still unclear whether more caudal structures may play a role in cognitive deficits, particularly in those cases where there is no evidence of hippocampal sclerosis. This work used a genetically selected rat strain for seizure susceptibility (Wistar audiogenic rat - WAR) and distinct behavioral (motor and memory-related tasks) and electrophysiological (inferior colliculus - IC) approaches to access acoustic primary integrative network properties. The IC neural assemblies’ response was evaluated by auditory transient (focusing on bottom-up processing) and steady-state evoked response (ASSR - centering on feedforward and feedback forces over neural circuitry). The results show that WAR displayed no disturbance in motor performance or hippocampus-dependent memory tasks. Nonetheless, WAR animals exhibited significative impairment for auditory fear conditioning along with no indicative of IC plastic changes between the pre-conditioning and test phases (ASSR coherence analysis). Furthermore, WAR's IC response to transient stimuli presented shorter latency and higher amplitude compared with Wistar; and the ASSR analysis showed similar results for WAR and Wistar animals under subthreshold dose of pentylenetetrazol (pro-convulsive drug) for seizure-induction. Our work demonstrated alterations at WAR IC neural network processing, which may explain the associated disturbance on auditory fear conditioning memory.